Language Policy and Minority Rights in Ukraine - Fodor Gyula; Фодор Дюло; Csernicsko Istvan; Csernicskó István; Черничко Степан (Polygraphcenter "LIRA", 2013)
Abstract. Ukraine de jure is a monolingual state, but de facto it is bi- or multilingual. Due to the high ratio of the Russian-speaking people, it is not surprising that the main problem of the ethnic and language policy in Ukraine is the status of the Russian minority and language. On August 8, 2012, the president of Ukraine, Viktor Yanukovych, signed the Law 5029-VI entitled “The Fundamentals of the State Language Policy”, which offers the opportunity of using the national minority languages in administrative units (counties, districts, etc.) where the number of their speakers reaches or exceeds 10%. The power of the law would comprise the languages of 18 national minorities. Though, in the present political situation, the change of legal language status in the country seems to be impossible.
http://real.mtak.hu/23920/
Keywords: Ukraine; language policy; minority rights